Evolution of the Molecular Biology of Brain Tumors and the Therapeutic Implications - Lichtor, Terry (IntechOpen, 2013)
A dramatic increase in knowledge regarding the molecular biology of brain tumors has been established over the past few years. In particular recent new avenues regarding the role of stem cells and microRNAs along with further understanding of the importance of angiogenesis, immunotherapy and explanations for the resistance of the tumors to chemotherapeutic agents and radiation therapy has been developed. It is hopeful that this new information will lead to efficacious treatment strategies for these tumors which remain a challenge. In this book a review of the latest information on these topics along with a variety of new therapeutic treatment strategies with an emphasis on molecular targeted therapies is provided.